Transformasi Layanan Administrasi Kependudukan Indonesia dalam Mewujudkan Konsep Welfare State: (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang Selatan) - Hanif Hardianto (Ajudikasi : Jurnal Ilmu Hukum, 2022)
The transformation of public services in the field of population administration began to be felt after the all-internet or online era began to bloom in Indonesia. This causes public service providers to be asked to make changes in the concept of serving the community by following the changing times. The research method used is qualitative research or sociological juridical. The primary data source is interviews with the South Tangerang City Population and Civil Registry Service, while the secondary data source is various legal book materials and statutory regulations. The results of the research can be found that the transformation of Indonesian population administration services has begun to lead to realizing the concept of "welfarestate" for the community, with the change in population administration services that previously used offline or the community was required to be physically present to take care of population administration, now with the all-internet era the organizers population administration implements services with an online system in order to reach the public so that services are more effective, efficient and excellent. The originality of this research is that people in today's era who are completely connected to the internet have resulted in the implementation of public services also having to follow it. The positive side of public services by being connected to the internet can make it easier for people to access population administration matters without coming physically in person. However, public services cannot fully use online services, population administration public services also require offline services in order to fulfill services for people who do not understand technology.